2022
DOI: 10.3390/ma15093062
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Self-Centering Performance of the SMA Fiber Reinforced ECC Composite Beam

Abstract: The combination of superelastic shape memory alloy fibers and ECC materials can form a new SMA fiber reinforced ECC composite material (SMAF-ECC) with good self-centering performance. In order to study the self-centering performance of the new composite material, 6 groups of pre-notch beam specimens were made for three-point bending cyclic loading tests, and the failure phenomenon, hysteresis curve, self-centering effect and influencing factors of the specimens were analyzed. The research results show that whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Chen et al [ 36 ] also proved the improvement in strength and ductility and the self-centering ability of SMA-ECC specimens. The author’s previous research [ 32 ] also confirmed the effectiveness of SMA fibers in improving the energy dissipation and self-centering ability of ECC beams.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Chen et al [ 36 ] also proved the improvement in strength and ductility and the self-centering ability of SMA-ECC specimens. The author’s previous research [ 32 ] also confirmed the effectiveness of SMA fibers in improving the energy dissipation and self-centering ability of ECC beams.…”
Section: Introductionmentioning
confidence: 59%
“…Compared with concrete or mortar, ECC has much larger tensile deformation capacity, so it is more compatible with SMA fibers. In addition, the crack distribution of ECC is wide and the crack width is small, which can enable more SMA fibers to participate in the work and reduce the difficulty of SMA fibers to close the crack [ 32 ]. On the other hand, SMA fibers can provide crack closure and self-centering capability for ECC, which can effectively solve the problems of residual deformation and residual cracks of ECC materials.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the SMAs were used to improve the vibrational and buckling behaviors of the designed composite. Later, extensive research was performed to investigate active control of SMA-based hybrid composite beams [ 6 , 7 , 8 , 9 ], plates [ 10 , 11 , 12 , 13 , 14 , 15 ], shell panels [ 16 ] and sandwich panels [ 17 , 18 ]. More recently, due to the wide application of SMAHC structures in engineering, theoretical frameworks, which are qualified for accurately analyzing their dynamic and static behaviors, have drawn extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…Author [16][17] conducted three-point bending cyclic loading tests and cyclic tensile tests on SMA/PVA-ECC specimens and found that SMA fibers with knot ends could fully exert their superelastic properties, providing hysteresis energy dissipation capacity for the specimens and achieving crack closure and bending self-recovery functions, significantly improving the maximum tensile stress of the dog-bone specimens.…”
Section: Introductionmentioning
confidence: 99%